Cytomorphology, osmotic fragility, glucose-6-phosphate dehydrogenase and oxidant/antioxidant status in postparturient haemoglobinuria in dairy cattle and buffaloes - A. I. Hassanin; M. H. Karam; N.-E. M. Aref (Bulgarian Journal of Veterinary Medicine)
The present study was carried out to elucidate the role of blood phosphorus (P), erythrocytic glucose-6-phosphate dehydrogenase (G6PD), glutathione peroxidase (GSH-Px), malonaldehyde (MDA), and nitric oxide (NO) on the integrity of the cell membranes of red blood cells (RBCs) and the develop-ment of postparturient haemoglobinuria (PPH) in dairy cattle and buffaloes. The study also aimed to demonstrate the association between these parameters and erythrocyte osmotic fragility. A total of 58 cows and buffaloes were included and categorised into control group (n=20) and diseased group (n=38). Complete history and clinical examination were conducted. Blood samples were collected and prepared accordingly to assess complete blood count (CBC), reticulocyte count, cytomorphology of RBCs, osmotic fragility, erythrocytic G6PD, GSH-Px, blood phosphorus (P), calcium (Ca), para-thormone (PTH), MDA and NO. The hallmark sign of diseased animals was the passage of red to coffee colored urine. CBC data revealed significant reduction (P<0.05) in the RBCs count, haemo-globin (Hb) concentration and packed cell volume (PCV) in the diseased group. Cytomorphological examination revealed strong evidence of regenerative anaemia including reticulocytosis and presence of nucleated RBCs in peripheral blood. The study demonstrated a marked increase in the osmotic fragility of RBCs in PPH. Biochemical data revealed a significant decrease (P<0.05) in the blood level of P, G6PD, GSH-Px, PTH and significantly increased (P<0.05) MDA in PPH. Ca:P ratio showed a marked disturbance in diseased buffaloes. The study also established a strong positive asso-ciation between the osmotic fragility index (OFI) and the blood MDA level. On the other hand, there was a strong negative association between OFI and blood levels of P and G6PD suggesting the impor-tant role of P, G6PD and oxidative stress in PPH etiopathogenesis. The study validated the hypothesis that phosphorus deficiency affected the blood G6PD level with subsequent alteration of glycolysis and generation of GSH-Px predisposing RBCs to oxidative damage and intravascular haemolysis.